Association of Asthma Control and Metered-Dose Inhaler Use Technique among Adult Asthmatic Patients Attending Outpatient Clinic, in Resource-Limited Country: A Prospective Study - Bezie Kebede; Girma Mamo; Abebaw Molla (Canadian Respiratory Journal)
Asthma is a heterogeneous disease which is characterized by chronic airway inflammation. It is a common chronic respiratory disease affecting 1–18% of population in different countries. It can be treated mainly with inhaled medications in several forms, including pressurized metered-dose inhaler (MDI). Patients encountered difficulty in using inhaler devices even after repeated demonstration and/re-evaluation. This could highly compromise patient treatment outcome/asthma control. To evaluate relationship between MDI use technique and asthma control among adult asthmatic patients who attend respiratory clinic in Jimma University Medical Center (JUMC), Southwest Ethiopia. A prospective observational study was conducted from March to August 22, 2018. All adult asthmatic patients who met the inclusion criteria were included in the study. Patient baseline assessment was conducted (patient demography, inhalation technique, adherence, and asthma control status). Inhalation technique was obtained using a standard checklist of steps recommended in National Institute of Health (NIH) guidelines. Patient adherence using asthma inhalation test and asthma control status was assessed by 2017 GINA guideline. Independent predictors of outcome were identified, strength of association between dependent and independent variables was determined by using ordinal logistic regression analysis, and statistical significance was considered at P<0.05. One hundred forty patients were included in the analysis. Among these, 26 (18.4%) patients were controlled, 65 (46.1%) partially controlled, and 35% uncontrolled. Proportion of patients with uncontrolled asthma were higher among inefficient as compared to efficient, whereas patients with controlled asthma were higher among efficient as compared to inefficient. Asthma control status is significantly associated with inhalation technique (P=0.006). Since most of the patients were inefficient and it is significantly associated with asthma control status, the hospital tried to adopt video MDI teaching program, and the patient should ask healthcare professionals how to take medication and they should bring their device to receive demonstration during visit. Health professionals should re-evaluate the patient during their hospital visit and encourage bringing their device to give demonstration.